Designing and implementing content-based courses in english with a non-language faculty at a public colombian university (2008)
This article reports the findings of an investigation into the experience of a group of eight professors from undergraduate programs in hard sciences who participated in a multi-site study to implement content-based (CB) courses in English. The professors, who had a high level of proficiency in English, worked in collaboration with language faculty. The data gathered from focus groups, class observations and in-depth interviews reveal some factors which influence the professors’ teaching practices, and the academic and professional gains they derived from this experience. Founded on the results, the researchers propose a mentoring program that supports professors in the development of CB courses in English. Key words: Content-based teaching in EFL, mentoring programs, professional development Este artículo presenta los resultados de una investigación sobre la experiencia de un grupo de ocho docentes de pregrado de ciencias exactas y naturales quienes participaron en un estudio de caso múltiple para implementar cursos de contenido en inglés. Los profesores, quienes tenían un alto nivel de competencia en inglés, trabajaron en colaboración con docentes de lenguas. Los datos que se obtuvieron de los grupos focales, de las observaciones de clase y de las entrevistas a profundidad muestran algunos de los factores que influyen en sus prácticas pedagógicas y los logros académicos y profesionales que se derivaron de esta experiencia. A partir de los resultados, los investigadores proponen un programa de apoyo tutorial que apoye a los docentes en el desarrollo de cursos de contenido en inglés. Palabras claves: Enseñanza del inglés a través de contenidos, programas de desarrollo profesional, desarrollo profesional